The Discourse of Kingship in Classical Greece - Atack, Carol (Routledge Monographs in Classical Studies, 2019)
Cover -- Half Title -- Series Page -- Title -- Copyright -- Contents -- Acknowledgements -- Abbreviations -- Introduction -- 1 King and cosmos in Herodotus -- Herodotus' 'monarchical model' and the 'despotic template' -- Differentiating kings and tyrants -- Kings, custom and order: Herodotus and Heraclitus -- Kings and knowledge -- Structure and cyclicality -- Kingship in the constitution debate -- Herodotus' studies of kingship -- Deioces, the model king of the Medes -- Psammetichus and Egyptian kingship -- Amasis and the burdens of divine kingship -- Kingship at the limits of the Greek world -- Conclusion -- 2 Monarchy on the democratic stage -- The Athenian political imaginary and drama -- The good king in the polis -- The king and the coherence of the polity: Aeschylus' Persians -- The king as the focus of supplication -- Greeks and others: Aeschylus' Suppliants -- The democratic king deconstructed: Euripides' Suppliants -- Kingship in Sophocles' Oedipus at Colonus -- Kingship and autochthony -- Cosmology and comedy -- Conclusion -- 3 The discourse of kingship in classical Athenian thought -- Structuring the Athenian past in time and space -- The Athenian past in rhetoric and philosophy -- The focus on Theseus -- Isocrates' Theseus -- The king as rhetorical exemplar for citizens -- Conclusion -- 4 Kingship and Socratic thought -- Antisthenes and single-person rule -- Xenophon's account of the 'kingly art' -- The discourse of kingship in Xenophon's Socratic works -- The craft of kingship in the Memorabilia -- Kingship in the Oeconomicus -- Plato and kingship as a master art -- Socrates' 'political craft' -- Basilikē technē in the Euthydemus and Republic -- The hunt for basilikē technē -- Conclusion -- 5 Virtue and monarchy -- Isocrates' model of virtue monarchy: the kings of Salamis -- The qualities of monarchy -- The qualities of the king.